Prion-like protein gene (PRND) polymorphisms associated with scrapie susceptibility in Korean native black goats. - Min-Ju Jeong; Yong-Chan Kim; Byung-Hoon Jeong (PLoS ONE, 2018)
The polymorphisms of the prion protein (PRNP) gene, which encodes normal prion proteins (PrP), are known to be involved in the susceptibility of prion diseases. The prion-like protein (Doppel) gene (PRND) is the paralog of the PRNP gene and is closely located downstream of the PRNP gene. In addition, the polymorphisms of PRND correlate with disease susceptibility in several animals. We analyzed the genotype and allele frequencies of PRND polymorphisms in 246 Korean native black goats and found a total of six single nucleotide polymorphisms (SNPs) with one novel SNP, c.99C>T. We observed linkage disequilibrium (LD) within and between loci. PRND c.28T>C, c.151A>G, and c.385G>C and PRND c.65C>T and c.286G>A were in perfect LD and we have reported for the first time strong LD between PRND and PRNP or prion-related protein gene (PRNT) loci. Specifically, between the PRND c.28T>C, c.151A>G and c.385G>C and the PRNP codon 143, PRND c.99C>T and the PRNP codon 102 or PRND SNPs (c.28T>C, c.151A>G and c.385G>C) and PRNT SNP (c.321T>C). Furthermore, we confirmed that the genotype distribution of the PRNP p.His143Arg was significantly different according to that of the PRND c.28T>C (P < 0.0001). Finally, using PolyPhen-2 and PROVEAN, we predicted that two non-synonymous SNPs, c.65C>T and c.286G>A, in the PRND gene can have a detrimental effect on Doppel. To the best of our knowledge, this is the first report of genetic characteristics of the PRND gene in Korean native black goats.